Pembakaran Terkendali Sebagai Metoda Alternatif dalam Pencegahan Kebakaran Hutan di Hutan Tanaman Acacia mangium - Saharjo, Bambang Hero (Jurnal Manajemen Hutan Tropika, 1999)
Prescribed burning was well done in Acacia mangium plantation without any trees damaged or dead and no natural regeneration found in the forest floor after fire. Fuel load 3 ton/ha and fuel bed depth 8 cm can be used as a standard for it. Flame temperature reached from 149 °C and 170 °C, and flame length 0.74-0.93 m can safe the plantation for any damage. Three months after burning there was an accumulation of fuel load in the forest floor, therefore 3 months interval is a good solution in preventing the forest from fire invasion.